Taxonomy and ecology of order surirellales (Bacillariophyceae) in tropical reservoirs in southeastern of brazil - de Morais, Krysna Stephanny; Bartozek, Elaine Rodrigues [UNESP]; Zorzal-Almeida, Stéfano; Bicudo, Denise C.; Bicudo, Carlos Eduardo de Mattos (FapUNIFESP (SciELO), 2018)
Aim: The aim of this study was to inventory the diatom species of order Surirellales present in the surface sediments of tropical reservoirs (São Paulo State, Brazil) and to correlate their distribution with environmental (pH, total phosphorus, and total nitrogen) and spatial predictors. Methods: Samplings were carried out in 31 reservoirs from 2009 to 2014. Vertical profile of water samples was collected in the summer and winter along the reservoirs, and their water column mean results were used to characterize each sampling site. We measured water transparency, euphotic zone, water depth, pH, dissolved oxygen, total nitrogen, and total phosphorus. Surface sediment samples (2 cm top) were collected for diatom analyses. A partial RDA was performed between species abundance data (response matrix) and environmental and spatial variables (predictor matrices). Results: 14 species of Surirellales were identified from the surface sediment samples, five of them being identified only at the genus level. Overall, partial RDA showed that the species distribution is constrained by both environmental and spatial predictors. Species were mainly ordinated in relation to pH and light availability. Conclusion: Our results demonstrated that the Surirellales species revealed ecological preferences to low nutrient concentrations, neutral to slightly acidic waters, and higher light availability. Moreover, our results suggest that both environmental and spatial factors are important for their species distribution.
Taxonomia e ecologia da ordem surirellales (Bacillariophyceae) em reservatórios tropicais no sudeste do brasil
Keywords: Brazil; Stenopterobia; Surface sediment; Surirella